Analysis of Factors Affecting Carbon Emission Disclosure in Indonesia - Wibowo, Rendi; Suhendro, Saring; Amelia, Yunia (Journal Of Accounting Management Business And International Research, 2022)
This study aims to analyze what factors affect the disclosure of carbon emissions in carbon intensive companies listed on the Indonesia Stock Exchange in the period 2016 - 2020 years. The method used in this study is a quantitative research method with literature studies both on the company's website and on the Indonesian stock exchange. The collection technique the data used is purposive sampling to determine the sample in this study. The sample used as many as 138 companies with data processing methods using analysis descriptive statistics, classical assumption test, hypothesis testing, and coefficient of determination test. Results of the research show that firm size, profitability, managerial ownership, and ownership institutions have a positive influence on the disclosure of carbon emissions. In addition, can it is known that the company's leverage harms the disclosure of emissions carbon while total asset turnover, environmental performance, regulators, and media exposure do not affect the disclosure of carbon emissions.